Pengaruh Loyalitas Fanbase Alwi Assegaf terhadap Sikap Menonton Sinetron Raden Kian Santang di MNCTV: Survei pada Akun Istagram @fsaai_officiall - Nugie Gustian; Amin Shabana (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
Mass media and the current information technology, can provide positive and negative impacts. One of them is the visual television program that can influence the public's viewing attitude. This study aims to measure the Influence of Alwi Assegaf's Fanbase Loyalty on the Attitude of Watching Raden Kian Santang, a television program that is famous for the presence of Alwi Assegaf as one of the main roles in it. This study uses a quantitative method by distributing questionnaires to active Alwi Assegaf fanbase members with a sample size of 84 people. This study has two variables, namely Fanbase Loyalty and Viewing Attitude. The audience loyalty variable in this study is measured using the dimensions of Internal Involvement, External Involvement, Desire to Acquire and Interaction. To measure the viewing attitude variable, this study uses the dimensions explained by Suryanto, namely, Cognitive, Affective and Conative. The results of the study indicate that Alwi Assegaf Fanbase Loyalty is a variable that has been studied and obtained a positive assessment, this has been proven through the total average value that has been calculated at 44.39, Attitude to watch Raden Kian Santang is a variable that has been studied and obtained a positive assessment, this has been proven through the total average value that has been calculated at 42.42, For a simple regression test, the results obtained were 0.826, which means that the relationship or correlation between the Alwi Assegaf Fanbase Loyalty variable has a high or strong influence on the Raden Kian Santang Watching Interest variable. For the hypothesis test, the results obtained were 1.663. The calculated t value (3.594)> t table (1.663) then it can be concluded that H0 is rejected and H1 is accepted, which shows that there is an influence between the Alwi Assegaf Fanbase Loyalty variable! (X) with the Attitude to Watch Raden Kian Santang